PELATIHAN KOMUNIKASI EFEKTIF DI SMA TAMAN SISWA SINGOSARI MEDAN - Herawati, Yayuk Widyastuti (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2023)
The purpose of holding this service is to help middle school English teachers create backgrounds for journals or scientific presentations, both national and international. This background creation training will train junior high school teachers to reflect on what has been done in the classroom. So it is hoped that when teachers have to teach and educate, they can also solve learning problems such as inappropriate techniques that make it difficult to raise students' grades, etc. The specific target to be achieved is to foster an academic and scientific atmosphere among junior high school English teachers in Malang. In this regard, teachers are expected to be able to teach and reflect on learning outcomes in the classroom. In relation to this, as an English teacher the teacher must be able to identify existing problems, determine alternative solutions to existing problems, and the research method or methodology that will be applied so that it can be successful. This media creation uses the background creation theory from Milnes (2014).